Teacher Professional Learning, Culturally Responsive/Sustaining Practices, and Indigenous Students’ Success: A Comparative Case-Study of New Zealand and Saskatchewan, Canada (Alberta Journal of Educational Research, 2021)
Employing a multiple instrumental case study approach, we document and analyze initiatives in Saskatchewan and New Zealand to enhance cultural responsiveness among White educators through professional learning initiatives undertaken as part of broader strategies to animate more equitable educational outcomes for Indigenous students. The findings of this research confirm the capacity of teachers to act as agents of change and highlight the potential of teacher professional learning to catalyze educational reform and innovation, ensuring that schools can indeed benefit students who have historically been underserved by public education. We conclude that the growing Indigenous presence in classrooms is a powerful driver of innovation, which offers the potential to transform curriculum, pedagogy, and teacher-student relationships for the benefit of all learners in these contexts and beyond.Key words: Indigenous students, teacher professional learning, culturally-responsive pedagogy, Saskatchewan, New ZealandEn utilisant une approche d'étude de cas instrumentale multiple, nous documentons et analysons des initiatives en Saskatchewan et en Nouvelle-Zélande visant à améliorer la sensibilité culturelle des enseignants blancs par le biais d'initiatives d'apprentissage professionnel entreprises dans le cadre de stratégies plus larges visant à produire des résultats éducatifs plus équitables pour les étudiants autochtones. Les résultats de cette recherche confirment la capacité des enseignants à agir en tant qu'agents de changement et soulignent le potentiel de l'apprentissage professionnel des enseignants à catalyser la réforme et l'innovation en matière d'éducation, garantissant ainsi que les élèves qui ont historiquement été mal desservis par l'éducation publique peuvent effectivement profiter des écoles. Nous concluons que la présence croissante des autochtones dans les salles de classe est un puissant moteur d'innovation qui offre la possibilité de transformer les programmes d'études, la pédagogie et les relations entre enseignants et élèves au profit de tous les apprenants dans ces contextes et au-delà.Mots-clés: élèves autochtones, apprentissage professionnel des enseignants, pédagogie adaptée à la culture, Saskatchewan, Nouvelle-Zélande